Evaluation of Nasal Resistance by Rhinomanometry before and after Endoscopic Sinus Surgery - Kaneda, Shoji; Sekine, Motoki; Saito, Kousuke; Murakami, Tomoaki; Yamamoto, Hikaru; Okami, Kenji; Furuya, Hiroyuki; Iida, Masahiro (International Journal of Practical Otolaryngology, 2019)
With the objective of identifying the factors affecting the nasal resistance in patients undergoing sinus surgery, we evaluated the data of 95 patients with chronic sinusitis who underwent endoscopic sinus surgery (ESS) between 2015 and 2018 at our hospital. We determined the nasal resistance by rhinomanometry and also patients' sensation of nasal obstruction before surgery and 3 months after the ESS. In total, 49 bilateral and 46 unilateral ESS procedures were performed, including ESS alone, ESS + septoplasty, and ESS + septoplasty + conchotomy. In addition, the surgical cases were classified into single sinus or polysinus surgery, and groups with or without polyps. We compared the nasal resistance and degree of change in the nasal resistance among the groups. The same comparisons were also conducted separately in cases with nasal resistance levels of >0.25 Pa/cm3/s. Nasal resistance improved following the ESS in both the bilateral and unilateral cases. In almost all the subgroups, the nasal resistance improved following ESS with the exception of the ESS with septoplasty group with nasal resistance levels of >0.25 Pa/cm3/s. The degree of change in the nasal resistance was not significantly different between the ESS alone, ESS + septoplasty, and ESS + septoplasty + conchotomy groups. Similarly, the degree of change in the nasal resistance was also not significantly different between the single sinus and polysinus surgery or between patients with and without polyps. Furthermore, there were no differences among the above groups of patients with >0.25 Pa/cm3/s either. The patients' sensation of nasal obstruction improved following the ESS. The nasal resistance measured by rhinomanometry was weakly correlated with the sensation of nasal obstruction prior to the ESS; however, the nasal resistance following the ESS and the degree of change of the nasal resistance following the ESS were not correlated with the sensation of nasal obstruction or the degree of change in the sensation of nasal obstruction. Future studies are needed for a precise clarification of the factors that affect nasal resistance.
Keywords: nasal obstruction; nasal resistance; rhinomanometry; before and after ESS